Teaching Narrative Text by Using Story Telling Method at Ninth Grade Students - Anrasiyana (STKIP PGRI SIDOARJO, 2021)
This research was aimed to investigate the used of storytelling in teaching narrative text in junior high school. This research employed a quantitative method with a true experimental design. The sample of this research was the 9th grade students at MTs. Miftahul Ulum Batang-Batang. There were 42 students involved in this research; 21 of them belonged to experimental class and 21 were belonged to control class. Therefore the speaking test and questionnaire were implemented as the research instrument in order to collect the data. The test was conducted twice, first test was pretest and the second was posttest. The result of this research indicated that teaching narrative text by using story telling method was effective